An imroved design for ZVT DC-DC PWM converters with snubber assisted auxiliary switch - Russi,J. (2005)
This paper proposes an improved design to calculate the snubber auxiliary elements of ZVT DC-DC PWM converters with snubber assisted auxiliary switch. The proposed improved design guidelines are based on the reduction of the conduction losses through the auxiliary circuit. It is accomplished by the unique location of the turn-off snubber capacitor, which is shared by both active switches. By means of this improved design guidelines the converter efficiency can be increased. An efficiency comparative analysis is carried out and the experimental results, obtained from 1 kW, 100 kHz laboratory prototypes, show a relevant improvement in converter efficiency compared to the original converter design. In addition, experimental results also confirm that with the improved design the ZVT PWM converters with snubber assisted auxiliary switch can be competitive with ZVT PWM converters with constant auxiliary voltage source (True PWM ZVS pole).